Public Debt, Sustainability and Economic Growth Theory and Empirics - Greiner, Alfred; Fincke, Bettina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Public debt has become a severe problem for a great many economies. While the effects of tax policies on the allocation of resources are readily derived, the mechanisms that make public deficits and debt influence the economy are not so easily understood. This book elaborates on the effects of public debt starting from the intertemporal budget constraint of the government. It is shown under which conditions a government can stick to the intertemporal budget constraint, and, then, demonstrated how public debt affects the growth process and welfare in market economies. The effects are derived for models with complete labor markets as well as taking into account labor market imperfections. The focus in this book is on fiscal policy issues, but it also deals with monetary policy aspects. The theoretical analysis is complemented with empirical time series analyses on debt sustainability and with panel studies dealing with the relationship between public debt and economic growth.
Introduction -- Sustainable Public Debt: Theory and Empirical Evidence -- Debt and Growth: A Basic Endogenous Growth Model -- Productive Government Spending, Public Debt and Growth -- Government Debt and Human Capital Formation -- Debt and Growth: Empirical Evidence -- Conclusion.
Keywords: Economics; Development Economics; Endogenous growth (Economics).; Macroeconomics; Finance; Economics/Management Science; Economic Growth; Macroeconomics/Monetary Economics; Development Economics; Public Finance & Economics; Economic Theory; Political Economy